Electronic structure and ultrafast dynamics of FeAs-based superconductors by angle- and time-resolved photoemission spectroscopy - Avigo, I.; Thirupathaiah, S.; Rienks, E. D. L.; Rettig, Laurenz; Charnukha, A.; Ligges, M.; Cortes, R.; Nayak, J.; Jeevan, H. S.; Wolf, T.; Huang, Y.; Wurmehl, Sabine; et al. (physica status solidi (b), 2017)
In this article, we review our angle- and time-resolved photoemission studies (ARPES and trARPES) on various ferropnictides. In the ARPES studies, we focus first on the band structure as a function of control parameters. We find near optimally “doped” compounds a Lifshitz transition of hole/electron pocket vanishing type. Second, we investigated the inelastic scattering rates as a function of the control parameter. In contrast to the heavily discussed quantum critical scenario, we find no enhancement of the scattering rate near optimally “doping.” Correlation effects which show up by the non-Fermi-liquid behavior of the scattering rates, together with the Lifshitz transition offer a new explanation for the strange normal state properties and suggests an interpolating superconducting state between BCS and BE condensation. Adding femtosecond time resolution to ARPES provides complementary information on electron and lattice dynamics. We report on the response of the chemical potential by a collective periodic variation coupled to coherent optical phonons in combination with incoherent electron and phonon dynamics described by a three temperature heat bath model. We quantify electron phonon coupling in terms of λ 〈ω〉2 and show that the analysis of the electron excess energy relaxation is a robust approach. The spin density wave ordering leads to a pronounced momentum dependent relaxation dynamics. In the vicinity of kf, hot electrons dissipate their energy by electron–phonon coupling with a characteristic time constant of 200 fs. Electrons at the center of the hole pocket exhibit a four time slower relaxation which is explained by spin-dependent dynamics with its smaller relaxation phase space. This finding has implications beyond the material class of Fe-pnictides because it establishes experimental access to spin-dependent dynamics in materials with spin density waves.
CRIS-Team Scopus Importer:2022-04-14
Keywords: angle-resolved photoemission spectroscopy; Electronic structure; iron-based superconductors